Isolation of Human Adult Stem Cells from Muscle Biopsy for Future Treatment of Urinary Incontinence - Sharifiaghdas, Farzaneh; Taheri, Maryam; Moghadasali, Reza (Urology Journal, 2011)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE FA <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Purpose: To find a suitable and cost-effective technique for isolation and culture of muscle-derived stem cells (MDSCs) obtained from muscle biopsy in large quantities. Materials and Methods: A small muscle biopsy was taken from 10 donor rectus muscles in patients undergoing open abdominal surgery for any reason and transported on ice to the laboratory. The isolation of MDSCs was performed by two techniques; preplate and tissue explants. Initially, the isolation was carried out by preplating technique. However, enzymatic digestion of muscle biopsy in preplate technique compromised the integrity of important surface antigens of resident muscle stem cells and led to dysfunctional sorted cells. Also, many of the cells were lost in this technique and low numbers of MDSCs were yielded upon processing. Thus, we changed condition of centrifuge, but it did not affect cell numbers and their integrities. To overcome these problems, the technique was changed to tissue explants technique. Results: During the first 4 days in explant medium culture, activated satellite cells detached, migrated, and slowly divided. The MDSCs proliferated around the native myofiber and after 2 to 3 weeks, individual muscle cells appeared elongated and fused to create large multinucleated myotubes. On immunofluorescent staining, these emerged cells were positive for desmin and Pax7 and flow cytometry analysis revealed that these cells were CD45-, CD56+, and variable in CD34. Conclusion: We concluded that tissue explant method is a suitable and costeffective technique for isolation and culture of MDSCs from muscle biopsy in large quantities.